2013
DOI: 10.1111/bjhp.12021
|View full text |Cite
|
Sign up to set email alerts
|

Many apples a day keep the blues away – Daily experiences of negative and positive affect and food consumption in young adults

Abstract: Eating fruit and vegetables may promote emotional well-being among healthy young adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
135
1
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(150 citation statements)
references
References 109 publications
8
135
1
6
Order By: Relevance
“…Hendy (2012) found that consumption of calories, saturated fat, and sodium was significantly associated with increase in negative mood two days later. White et al (2013) find that eating fruit and vegetables one day is associated with a positive mood the next day. 14 Another limitation of this study is measurement error in data because self-reported measures of weight and height rather than actual measures are used in the BRFSS.…”
Section: Data and Empirical Strategymentioning
confidence: 85%
“…Hendy (2012) found that consumption of calories, saturated fat, and sodium was significantly associated with increase in negative mood two days later. White et al (2013) find that eating fruit and vegetables one day is associated with a positive mood the next day. 14 Another limitation of this study is measurement error in data because self-reported measures of weight and height rather than actual measures are used in the BRFSS.…”
Section: Data and Empirical Strategymentioning
confidence: 85%
“…Furthermore, a longitudinal study (89) has shown that a high level of dispositional optimism was associated with greater FV intake. Finally, using lagged analyses, White et al (60) also found that positive affect (measured using daily diaries over 21 d) was predicted by FV intake on the preceding day and not vice versa.…”
Section: Observational Evidence: Longitudinal Studiesmentioning
confidence: 97%
“…Innovative research by Tamlin Conner and collaborators 14 has found-using data on daily food diaries on 281 students tracked over a 3-week period-that a high level of fruit and vegetable consumption appears to be predictive of greater emotional well-being on the following day. Various cross-sectional papers have also pointed to the possible existence of a statistical connection between psychological well-being and the amount of fruits and vegetables eaten, and have shown that this correlation survives the inclusion of a large number of covariates.…”
mentioning
confidence: 99%